Calidad de sueño y su efecto en el rendimiento académico de estudiantes de Enfermería de la Universidad Nacional de Loja - Chacón Peralta, Michelle Estefanía (2022)
Sleep quality is a determining factor of health. It refers to the fact of sleeping well at night and performing well during the day. For this reason, the purpose of this research was to analyze the sleep quality and its effect on the students’ academic performance from Nursing Career at National University of Loja. This study was based on a descriptive-relational, quantitative, and cross-sectional methodology; in which 160 Nursing students were surveyed. The information was collected through an instrument called "Pittsburgh Sleep Quality Index", with an internal validity of 0.83. In addition, the files of the Career were reviewed to obtain the data of the academic performance. To establish the relationship between the variables studied, the Chi square statistic was used with a p value of 0.05. The results found show that: 76% correspond to the female sex, 59% are in the age range from19 to 22 years and 21% correspond to the fifth cycle of training. In relation to the sleep quality, it was determined that 84% have poor quality. Regarding academic performance, 55% have a good performance; When the non-parametric statistical test was applied, it was determined that there is no significant association between the variables investigated. Therefore, based on the results obtained, an intervention proposal was generated that contributes to the improvement of sleep quality. In conclusion, the students’ academic performance can be affected by different factors; however, in this case the sleep quality was not a determining factor, even though the results showed poor quality in a considerable percentage